The Analysis of Students' Perspective and Problems in English Pronounciation - Siti Fatimah (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2020)
Individual’s English pronunciation is influenced by various causes such as locality, early influences, and environment. Specifically, native Indonesians who learn English since they are in elementary school reveal that they still have problems to pronounce some English words. Hence, this study was conducted under the consideration of the important role of pronouncing English well by focusing on students’ perspectives and problems in English pronunciation, and their causes. This study employed descriptive qualitative by collecting the data from the questionnaire and interview with 10 students in the first semester at one of the higher education institutions in Cirebon. This study aims at discovering the problems faced by students in pronouncing English words and their causes appeared. The result shows that based on students’ perspective in learning pronunciation, 50% of students claimed that pronunciation course had a significant effect for their pronunciation and the rest 50% believed that there was no effect in their pronunciation. Additionally, based on their pronunciation problems, 60% of students always found difficulty in pronouncing English words, while the rest 40% found it easy. The causes of their problems were their mother tongue interference, sound system differences between LI and L2, and unknow how to read the phonetic transcription.